Live birth after treatment of a spontaneous ovarian heterotopic pregnancy: A case report - Inês Ramalho; Iolanda Ferreira; João Paulo Marques; Maria João Carvalho; António Lobo; Teresa Rebelo; José Paulo Moura; Fernanda Águas (Elsevier, 2019)
Spontaneous heterotopic pregnancies occur in about 1/30000 pregnancies, with the ovarian subtype comprising 2.3% of the total.We report the case of a healthy 32-year-old woman, gravida 4, para 3, who presented to the emergency room with severe abdominal pain. Two weeks earlier, pelvic ultrasound had revealed a 6-week intrauterine pregnancy. She was hemodynamically stable, but had rebound tenderness on the right iliac fossa. Transvaginal ultrasound revealed an evolutive intrauterine pregnancy with a gestational age (GA) of 8 weeks, with a synchronous evolutive adnexal pregnancy of the same GA and some free fluid in the pouch of Douglas. She underwent an urgent laparoscopy which showed an intact gestational sac containing an embryo on the right ovary associated with mild hemoperitoneum. An ovarian wedge resection was performed to preserve ovarian tissue. The intrauterine pregnancy had no complications and the patient delivered vaginally at term.Heterotopic pregnancy is potentially life-threatening. Despite being extremely rare after natural conception, and even more so in the absence of major risk factors, it should be considered in any pregnant woman with abdominal pain. A high index of suspicion is important for a prompt diagnosis, selection of the appropriate surgical treatment and successful obstetric outcomes. Keywords: Heterotopic pregnancy, Ovarian pregnancy, Laparoscopic management